Feasibility of establishing a rehabilitation programme in a Vietnamese intensive care unit - Anh, NTK; Yen, LM; Nguyen, NT; Nhat, PTH; Thuy, TTD; Phong, NT; Tuyen, PT; Yen, NH; Chambers, M; Hao, NV; Rollinson, T; Denehy, L; et al. (Public Library of Science, 2021)
Increasing numbers of people are surviving critical illness throughout the world, but survivorship is associated with long-term disability. In high-income settings physical rehabilitation is commonly employed to counter this and improve outcomes. These utilize highly-trained multidisciplinary teams and are unavailable and unaffordable in most low and middle income countries (LMICs). We aimed to design a sustainable intensive care unit (ICU) rehabilitation program and to evaluate its feasibility in a LMIC setting. In this project patients, care-givers and experts co-designed an innovative rehabilitation programme that can be delivered by non-expert ICU staff and family care-givers in a LMIC. We implemented this programme in adult patient with patients with tetanus at the Hospital for Tropical Diseases, Ho Chi Minh City over a 5-month period, evaluating the programme's acceptability, enablers and barriers. A 6-phase programme was designed, supported by written and video material. The programme was piloted in total of 30 patients. Rehabilitation was commenced a median 14 (inter quartile range (IQR) 10-18) days after admission. Each patient received a median of 25.5 (IQR 22.8-34.8) rehabilitation sessions out of a median 27 (22.8-35) intended (prescribed) sessions. There were no associated adverse events. Patients and staff found rehabilitation to be beneficial, enhanced relationships between carers, patients and staff and was deemed to be a positive step towards recovery and return to work. The main barrier was staff time. The programme was feasible for patients with tetanus and viewed positively by staff and participants. Staff time was identified as the major barrier to ongoing implementation.